Severe Acute Respiratory Syndrome Coronavirus 2 Infection Versus Vaccination in Pregnancy: Implications for Maternal and Infant Immunity . (10th May 2022) - Conti, Maria Giulia; Terreri, Sara; Terrin, Gianluca; Natale, Fabio; Pietrasanta, Carlo; Salvatori, Guglielmo; Brunelli, Roberto; Midulla, Fabio; Papaevangelou, Vassiliki; Carsetti, Rita; Angelidou, Asimenia
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has been associated with adverse maternal and neonatal outcomes, yet uptake of SARS-CoV-2 vaccines during pregnancy and lactation has been slow. As a result, millions of pregnant and lactating women and their infants remain susceptible to the virus. Methods: We measured spike-specific immunoglobulin G (anti-S IgG) and immunoglobulin A (anti-S IgA) in serum and breastmilk (BM) samples from 3 prospective mother-infant cohorts recruited in 2 academic medical centers. The primary aim was to determine the impact of maternal SARS-CoV-2 immunization vs infection and their timing on systemic and mucosal immunity. Results: The study included 28 mothers infected with SARS-CoV-2 in late pregnancy (INF), 11 uninfected mothers who received 2 doses of the BNT162b2 vaccine in the latter half of pregnancy (VAX-P), and 12 uninfected mothers who received 2 doses of BNT162b2 during lactation. VAX dyads had significantly higher serum anti-S IgG compared to INF dyads ( P  < .0001), whereas INF mothers had higher BM:serum anti-S IgA ratios compared to VAX mothers ( P  = .0001). Median IgG placental transfer ratios were significantly higher in VAX-P compared to INF mothers ( P  < .0001). There was a significant positive correlation between maternal and neonatal serum anti-S IgG after vaccination ( r  = 0.68, P  = .013), but not infection. Conclusions: BNT161b2 vaccination in late pregnancy or lactation enhances systemic immunity through serum anti-S immunoglobulin, while SARS-CoV-2 infection induces mucosal over systemic immunity more efficiently through BM immunoglobulin production. Next-generation vaccines boosting mucosal immunity could provide additional protection to the mother-infant dyad. Future studies should focus on identifying the optimal timing of primary and/or booster maternal vaccination for maximal benefit. Abstract : BNT161b2 vaccination in late pregnancy or lactation may confer enhanced systemic immunity as evidenced by higher maternal and neonatal serum spike-specific immunoglobulin levels compared to natural infection. Future vaccines should also target mucosal immunity for maximal benefit.